The personality puzzle: a comprehensive analysis of its impact on three buying behaviors - Aquino, Sibele D.; Lins, Samuel (Frontiers in Psychiatry, 2023)
This study aimed at examining the role of personality traits in impulsive buying, compulsive buying, and panic buying simultaneously during the COVID-19 pandemic. At the beginning of the third confinement announced by the Portuguese government, 485 Portuguese answered in this study, mean age of 41.9 years (min=18, max=84; SD=12.9), and 29.9% were men.Analyzes were carried out to investigate the association of Big Five's personality factors with impulsive buying, compulsive buying, and panic buying. Results showed that the three buying behaviors under study have significant and positive correlations between them, and they also correlate with different personality traits. The association of each Big Five factor on buying behaviors differed. While conscientiousness was negatively and openness was positively associated with impulsive buying, conscientiousness was negatively associated with compulsive buying, agreeableness was positively associated with panic buying, and neuroticism correlated positively with all consumer behaviors. Understanding the personality traits that contribute to the development of a disorder may provide valuable insight into preventive measures and effective treatment approaches for some debilitating disorders. This study opens ways for investigating impulsive buying and compulsive buying by relating them to panic buying. It discusses the three different buying behaviors during the COVID-19 pandemic and future consumer research directions involving other variables.